Silting at the Dock of the Bay: Mud, Mudslinging, and the Fight for the San Francisco Waterfront, 1853–63 - Nelson, Derek Lee (The Northern Mariner / Le marin du nord, 2025)
Between 1853 and 1863, no issue divided San Franciscans as much as the Bulkhead Bill (or Parsons Plan) that called for a seawall to wrap around the entire waterfront. The bill’s most controversial feature would have allowed a few businessmen to monopolize all waterfront transactions for 50 years as compensation for building the expensive bulkhead. By contrast, opponents characterized it as a scheme to fleece the city of revenue. On the surface, the bulkhead fight appears to be an urban question. But under the surface, it was at the core about sedimentation and the changing nature of San Francisco Bay.